Pengaruh perencanaan dan pelaksanaan terhadap penyerapan anggaran - Arsad, Rafli; Blongkod, Harun; Pakaya, Lukman (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to determine whether planning and implementation affect budget absorption in Gorontalo regency regional apparatus organizations. The population in this study is the Gorontalo Regency Regional Apparatus Organizations and based on sample criteria are Budget Users, Heads of the Finance Sub-Sector, Staff of the Finance Sector, Heads of the Planning Sub-Sector, Planning Staff, Secretary, Treasurer, Activity Technical Implementation Officer, and Budget Sector Officer, totaling 112 respondents. The test was carried out using a descriptive analysis method using Structure Equations, and Modeling with the assistance of the AMOS 24.0 program. The results of this study prove that planning has no positive or significant effect on budget absorption. Implementation has a positive and significant effect on budget absorption.